Emerging therapeutic paradigms to target the dysregulated Janus kinase/signal transducer and activator of transcription pathway in hematological malignancies. Issue 9 (September 2014) - Mughal, Tariq I.; Girnius, Saulius; Rosen, Steven T.; Kumar, Shaji; Wiestner, Adrian; Abdel-Wahab, Omar; Kiladjian, Jean-Jacques; Wilson, Wyndham H.; Van Etten, Richard A.
Abstract Over the past decade, there has been increasing biochemical evidence that the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway is aberrantly activated in malignant cells from patients with a wide spectrum of cancers of the blood and immune systems. The emerging availability of small molecule inhibitors of JAK and other signaling molecules in the JAK/STAT pathway has allowed preclinical studies validating an important role of this pathway in the pathogenesis of many hematologic malignancies, and provided motivation for new strategies for treatment of these diseases. Here, a round-table panel of experts review the current preclinical and clinical landscape of the JAK/STAT pathway in acute lymphoid and myeloid leukemias, lymphomas and myeloma, and chronic myeloid neoplasms.